The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.chemmater.0c02993
|View full text |Cite
|
Sign up to set email alerts
|

Polar Structure Formation in Solid Solution of Strontium-Substituted Fluorapatite–Gelatin Composites: From Structural and Morphogenetic Aspects to Pyroelectric Properties

Abstract: Strontium-substituted apatite–(CaF)–gelatin composites have been synthesized within a gelatin gel using the double-diffusion technique. All experimental parameters were kept constant while systematically varying the strontium/calcium molar ratio in solution. The effect of the presence of strontium ions in the growth solution on composition, morphogenesis, and morphology as well as pyroelectric properties of synthetic aggregates was systemically analyzed. It was shown that strontium ions significantly inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…[14][15][16] With the aim to utilize an anti-acid biomimetic coprecipitation nano particle, the inner carbonates were further selected as mixed strontium (Sr) and calcium carbonates as the addition of Sr 2+ is reported to enhance crystal anisotropy. 18 Our previous research also suggested promoting osteogenic differentiation by adding SrCO 3 . 19 To release the silica/calcium (strontium) carbonate coprecipitation nanoparticles (Si/Ca(Sr) NPs) onto dentine surfaces, the present study developed an all-in-one strategy fabricating the mineralized nano cellulose fiber (NCF) mats which can release functional Si/Ca(Sr) NPs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[14][15][16] With the aim to utilize an anti-acid biomimetic coprecipitation nano particle, the inner carbonates were further selected as mixed strontium (Sr) and calcium carbonates as the addition of Sr 2+ is reported to enhance crystal anisotropy. 18 Our previous research also suggested promoting osteogenic differentiation by adding SrCO 3 . 19 To release the silica/calcium (strontium) carbonate coprecipitation nanoparticles (Si/Ca(Sr) NPs) onto dentine surfaces, the present study developed an all-in-one strategy fabricating the mineralized nano cellulose fiber (NCF) mats which can release functional Si/Ca(Sr) NPs.…”
Section: Introductionmentioning
confidence: 94%
“… 14–16 With the aim to utilize an anti-acid biomimetic co-precipitation nano particle, the inner carbonates were further selected as mixed strontium (Sr) and calcium carbonates as the addition of Sr 2+ is reported to enhance crystal anisotropy. 18 Our previous research also suggested promoting osteogenic differentiation by adding SrCO 3 . 19 …”
Section: Introductionmentioning
confidence: 94%